Aphron properties and application of surfactant drilling fluids in depleted reservoirs - Mutter, Waleed K.; Almahdawi, Faleh H. M.; Ali, Jagar A. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Aphron drilling fluids (ADFs) are finding increasing application in science engineering fields because of their distinctive characteristic. As the interest in the application of aprons-based fluids continues to grow, there is a decisive need to advance a deeper understanding of the factors affecting their behavior and properties, especially for successful petroleum industries, such as drilling depleted reservoirs and production. This study delves into investigating the density, rheological behavior and properties, filtration properties, bubble size, and their distribution of Aphrons-drilling fluids utilizing two ionic surfactants. Sodium Dodecyl Benzene Sulfate (SDBS) as an anionic surfactant, Cetyl Trimethyl Ammonium Bromide (CTAB) as a cationic surfactant, described as environmentally friendly, in Iraqi depleted reservoirs drilling. With an emphasis on the concentrations balance between Aphron generator (SDBS) and Aphron stabilizer (CTAB), the study analyzes the behavior and characteristics of Aphron drilling fluid. The investigation demonstrates that adding SDBS and CTAB reduces system density by 28%, owing to microbubbles production which is utilized with near-balance drilling. Rheological testing reveals that shear-thinning behavior in all Aphron samples improved, and the presence of SDBS affects the fluid's internal friction, gel strength, and short-term gel structure. Filtering control characteristic study demonstrates that the presence of microbubbles significantly minimizes fluid loss by 33% with 0.20% SDBS during filtering. Bubble size and dispersion studies demonstrate that 0.20% SDBS concentration, along with 0.30% CTAB, gives the best microbubble size and distribution. These findings suggest that Aphron fluids will be a promising innovation in petroleum industries, during actual drilling operations in Iraqi depleted oilfields.